terms To Speech Pathology And Speech Defectsin The Concise Dictionary By Abdeljalil Mortad - Sabaa , Fatima Zahra (El Omda in Linguistics and Discourse Analysis, 2026)
Given the importance of linguistic pathology and its role in communication, many Arabic linguists have made efforts to track its terminology and find ways to treat it. Some contemporary researchers have worked hard to create specialised dictionaries that translate its terminology and explain its concepts to learners. Algerian academic researcher Professor Dr. Abdeljalil Mortad is among those who have taken an interest in this field in his Concise Dictionary of Linguistic Terms, which contains many terms related to speech disorders and pronunciation defects and presents them to readers and university students with explanations and details. Therefore, this study focuses on these terms and records their translations and explanations according to the dictionary author's point of view.